PERSEPSI WÂQIF DALAM BERWAKAF TUNAI - Yuke Rahmawati (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2013)
One of the provision contained in the Act 41 Year 2004 on Waqf is the permissibility of giving waqf in cash. This article describes various perceptions, taking into account of the strengths, weaknesses, opportunities, and challenges of cash waqf. Opportunity factors include the management and empowerment opportunities cash waqf as a form of new investment. The concept of fiqh is flexible and dynamic, therefore the waqf as a great potential to be developed according to the needs of the time. Aside of that is disadvantage factors such as absence of the of Muslim’s opinion on the issue.DOI: 10.15408/aiq.v5i1.2558